NOTARY LIABILITY FOR IRREGULARITIES IN THE DEED OF MEETING RESOLUTION STATEMENT (ANALYSIS OF THE ENGINEERING RESULTS OF THE COMPANY'S GENERAL MEETING OF SHAREHOLDERS) - Jamiatur Robekha; Chandra Yusuf; Frengki Hardian (SEAN Institute, 2023)
A notary is inseparable from him in making Minutes of Deeds. Minutes of the Deed is the original deed containing the signatures of the appearers, witnesses and notaries, which are kept as part of the notary's protocol. The minutes of the deed also include the number, date, and month of the year whose function is to guarantee certainty that the parties and appearers have met on that date, month, year and time. This study aims to obtain information and analyze laws and regulations regarding Notary Liability for Irregularities in the Deed of Statement of Meeting Resolutions: Engineering Analysis of the Results of the Company's General Meeting of Shareholders. By using the approach method in this study is a normative juridical approach. The formulation of the problem in this research is how is the validity of the Deed of Statement of Meeting Resolutions which becomes evidence in the Notary Deed? and What is the Notary's Responsibility for Irregularities in the Deed of Statement of Meeting Resolutions made based on engineered evidence? Deed of Statement of Meeting Resolutions, referred to as (PKR) is the result of the minutes of the General Meeting of Shareholders (GMS) made privately and then outlined in a Notary deed. This can be conveyed to the party from the Limited Liability Company concerned to be given directly through the GMS. The notary must pay attention in detail that the recipient of the power of attorney is an authorized representative of a Limited Liability Company (PT) and has expertise in making deeds. However, in practice and based on the reality in society, what is done by the Notary is still not in accordance with the procedures required by law or makes mistakes that result in losses for interested parties and the Notary himself. For Notaries. drag the Notary into something. Legal liability due to errors and carelessness, whether intentional or unintentional.